2014
DOI: 10.1007/s12011-014-9900-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc-Bearing Zeolite Clinoptilolite on Growth Performance, Nutrient Retention, Digestive Enzyme Activities, and Intestinal Function of Broiler Chickens

Abstract: This study was conducted to investigate the effect of zinc-bearing zeolite clinoptilolite (Zn-ZCP) on performance, growth performance, nutrient retention, digestive enzyme activities, and intestinal function in broiler chickens. A total of 180 1-day-old Arbor Acres chickens were randomly divided into three groups with six replicates of ten birds for a 21-day feeding period. Birds were fed a basal corn-soybean meal diet (29.1 mg of Zn per kilogram of diet) without supplemental zinc (control) or the same diet su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 44 publications
0
15
0
4
Order By: Relevance
“…However, there are several reports that demonstrate that higher Zn levels (60-180 ppm) produce better immune status in broiler chickens (Feng et al, 2010;Tang, Wen, Li, Wang, & Zhou, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are several reports that demonstrate that higher Zn levels (60-180 ppm) produce better immune status in broiler chickens (Feng et al, 2010;Tang, Wen, Li, Wang, & Zhou, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…criterion [5,12]. However, there are several reports that demonstrate that higher Zn levels [60-180 ppm] produce better immune growth performance and intestinal function of broiler chickens [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…; Tang et al . ,b). Our previous researches have shown that ZnCP could promote growth performance of broilers infected with Salmonella pullorum (Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…), increase the endogenous digestive enzyme activity (Tang et al . ) and even can replace the antibiotics used in poultry production (Tang et al . ).…”
Section: Introductionmentioning
confidence: 99%